Intraocular pressure-lowering efficacy of bimatoprost 0.03% and travoprost 0.004% in patients with glaucoma or ocular hypertension. Issue 11 (6th July 2006) - Cantor, L B; Hoop, J; Morgan, L; WuDunn, D; Catoira, Y
Abstract : Aim: To evaluate the efficacies of bimatoprost and travoprost for lowering of intraocular pressure (IOP) for the treatment of glaucoma and ocular hypertension. Methods: Prospective, randomised, investigator-blinded, parallel-group clinical trial. After completing a washout of all glaucoma drugs, patients (n = 157) were randomised to bimatoprost or travoprost for 6 months. Visits were at baseline, 1 week, and 1, 3 and 6 months. IOP was measured at 09:00 h at each visit and also at 13:00 and 16:00 h at baseline and at 3 and 6 months. Results: No significant between-group differences were observed in IOP at baseline, at 09:00, 13:00 or 16:00 h (p⩾0.741). After 6 months, both drugs significantly reduced IOP at every time point (p⩽0.001). After 6 months, mean IOP reduction at 09:00 h was 7.1 mm Hg (27.9%) with bimatoprost (n = 76) and 5.7 mm Hg (23.3%) with travoprost (n = 81; p = 0.014). At 13:00 h, mean IOP reduction was 5.9 mm Hg with bimatoprost (25.3%) and 5.2 mm Hg (22.4%) with travoprost (p = 0.213). At 16:00 h, the mean IOP reduction was 5.3 mm Hg (22.5%) with bimatoprost and 4.5 mm Hg (18.9%; p = 0.207) with travoprost. Both study drugs were well tolerated, with ocular redness the most commonly reported adverse event in both treatment groups. Conclusions: Bimatoprost provided greater mean IOP reductions than travoprost.